(untitled) (EU and comparative law issues and challenges series (ECLIC), 2020)
Financial crimes represent a significant problem at the EU level since they are damaging the integrity of the financial sector. In that context, it should be noted that there is a range of offences concerning financial crimes, so it became undisputed that such criminal activities should be prescribed in a comprehensive manner at the EU level. In that regard, it is worthwhile noting that Directive (EU) 2017/1371 on the fight against fraud to the EU’s financial interests by means of criminal law establishes the definition of criminal offences concerning combating fraud and other illegal activities affecting the EU’s financial interests. This is the reason why the first part of the paper is dedicated to the analysis of the criminal offences affecting the EU’s financial interests. However, the prescribed list of financial crime in Directive (EU) 2017/1371 represented only required but not the sufficient step for combating this type of criminal activities since there was a lack of legal possibilities for national and European authorities to access to relevant financial information as well as the lack of cooperation between them. On these grounds, the Directive (EU) 2019/1153 laying down rules facilitating the use of financial and other information for the prevention, detection, investigation or prosecution of certain criminal offences was adopted on 20 June 2019. For that reason, the second part of the article deals with the legal measures referred to in Directive (EU) 2019/1153 concerning the possibilities for the access by competent authorities to financial information as well as the conditions for the exchange of information between competent authorities and financial intelligence units as well as between financial intelligence units and Europol. Furthermore, since the protection of the financial interests by means of criminal law, cannot be sufficiently achieved only with individual measures adopted by Member States, it seems compulsory to take into consideration significant improvements achieved in this area at international level in order to examine whether the new EU framework is in compliance with existing international standards. Finally, since the Republic of Serbia has, in the context of accession and negotiations process to EU, recently amended the framework concerning criminal offences with regard to combatting fraud and other illegal activities affecting the financial interests, the third part of the paper is dedicated to the analysis of the national framework in order to examine its compliance with EU framework. In concluding remarks, it is noted that although in the recent period there have been significant improvements in the framework on the protection of the EU financial interests against financial crimes there is still a lack of effective implementation of adopted standards. Bearing in mind the above, some recommendations for accelerating the implementation of adopted measures are listed.